Accumulation of GAS5 in exosomes is a marker of apoptosis induction - Koldemir, Oguz (Biomed Rep, 2017)
Long non-coding RNAs (lncRNAs) are key regulatory molecules in many fundamental cellular processes and their deregulation is assumed to contribute to carcinogenesis. Exosomal lncRNAs are thought to be involved in the dissemination of cell signals to control local cellular microenvironments. In the current study, exosomal expression of growth arrest specific 5 (GAS5), an inhibitor of cell proliferation and promoter of apoptosis, was evaluated in apoptotic processes initiated by different mechanisms. Therefore, MCF-7 and MDA-MB-231 breast cancer cells were treated with Taxol (2 and 10 nM) and bleomycin (2 and 10 ng/ml) for 24 h. Following cell viability determination and measurement of apoptosis, cellular and exosomal expression levels of GAS5 were investigated using a quantitative polymerase chain reaction assay. The findings indicate that Taxol is more toxic than bleomycin at the indicated doses and the effect was more evident in the MCF-7 cells. Despite varying toxicity rates, comparable levels of apoptotic nucleosomes were measured between Taxol- and bleomycin-treated cells. Upon drug treatment, cellular expression levels of GAS rose (≤1.5-fold) in the two cell lines. It appears that even a small increase in cellular expression leads to exosomal enrichment, as the accumulation of GAS5 in exosomes was marked in the MCF-7 cells (≤5.8-fold). Compared with the MCF-7 cells, the extent of GAS5 enrichment in the exosomes secreted from MDA-MB-231 cells was moderate (≤1.9-fold), potentially as a result of reduced cell death. The present study indicates that GAS5 accumulation in exosomes is a prevalent event in apoptotic processes that are initiated by different mechanisms.